Impact of Covid - 19 Pandemic on Medical Training and Well-Being of Medical Students - Ghay, Richa; Kaur, Manjinder; Thaman, Varidhi; Singh, Muskan (International Journal of Innovative Research in Medical Science, 2022)
Introduction: The present study was undertaken to decipher the Impact of revamping teaching-learning modalities on undergraduate medical students and their well-being as a response to the COVID-19 pandemic. Methods: A Cross-sectional online survey was designed and validated. An online survey was constructed through google forms which were sent to undergraduate medical students through electronic media, emails, and WhatsApp groups. The questions formulated were both open and close-ended. The questions focussed on the well-being of students as well as on online teaching learning and assessment. Results: Students were mainly stressed, bored and irritable. Mental well-being was the most affected. Most of their free time was spent surfing the internet and on mobile. Baking and cooking became primary hobbies followed by drawing and painting. Family, music, and exercise became the chief source of a mental boost. Zoom synchronous classes and google classroom asynchronous classes were chiefly provided to students in various medical institutes. Most students used mobiles to attend online classes and this led to a lot of eye strain. The PowerPoint presentations and videos used were insufficient to understand the practical and clinical aspects. Assessments were mainly MCQs, short and long answer questions, and assignments. Students hoped for more clinical classes. Conclusion: Online classes were well accepted with the main complaint of no patient interaction and less gain of psychomotor skills. They affected the mental makeup of the students. Medical education can’t do without patient, teacher, and peer contact. The teaching learning and assessment should see a paradigm shift even in post covid era.